Piracy déjà vu. The reemergence of the conflict between users and platforms - Prosperi, Gabriele (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
In 1984, the United States Supreme Court issued a landmark ruling in Sony Corp. of America v. Universal City Studios, Inc., known as the Betamax case, which marked a turning point in access rights and copyright (Greenberg 2010). Major film studios had sued Sony, claiming that the videocassette recorder infringed on copyright by allowing users to record and store television programs without authorization, thereby undermining the commercial value of the works. However, the Court ruled that the use of the new technology fell under fair use, thereby legitimizing home recording. Today, in a kind of reversed cultural déjà vu, the evolution of OTT platform policies is expanding the notion of “piracy” to encompass practices that were until recently considered legitimate, such as account sharing among family and friends. Recent restrictions on shared accounts and the introduction of lower-cost subscription plans supported by targeted advertising aim to protect revenues and exert tighter control over user behavior (Lobato and Lotz 2021). This shift – markedly at odds with the initially more permissive approach adopted by these services – fits within a broader return to past economic models (Barra 2024), redefining content access in increasingly exclusive and conditional terms: the goal is to maximize revenue by encouraging adoption of premium options and introducing scarcity to increase perceived content value. As early as the 2000s, informal distribution systems (P2P networks, cyberlockers) had a similar impact, offering content for free (often illegally) and monetizing through on-site advertising and premium plans. Today’s practices – such as Disney+ preventing the use of ad-blockers and Netflix introducing “extra users” – reveal platforms’ growing interest in controlling and monetizing internal ad spaces, shifting the boundaries between acceptable consumption and perceived violations. What will be the effects of these policies on user behavior? Will platforms’ current decisions lead to the reclassification of certain social practices as illegitimate, turning once-accepted behaviors into “pirate” activities? If we are witnessing a new “age of piracy,” it no longer concerns only free access to copyrighted content, but raises broader questions about everyday practices of online consumption. As streaming shifts from a new medium to a new traditional medium, perceptions of illegality and “counterfeiting” are now extending to new technological frontiers, such as those defined by artificial intelligence (Cave et al. 2018), shifting the competition from content distribution to content production. This gives rise to a confrontation between new “formal” and “informal” actors, generating a tension reminiscent of past concerns about piracy – now at the level of content creation – and redefining public perception of the cultural product, questioning what is considered legitimate or illegitimate in creative reuse and technological innovation.